Lack of genotoxicity of formocresol, paramonochlorophenol, and calcium hydroxide on mammalian cells by comet assay - Ribeiro, Daniel Araki [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Wolters Kluwer, 2004)
Formocresol, paramonochlorophenol, and calcium hydroxide are widely used in dentistry because of their antibacterial activities in root canal disinfection. However, the results of genotoxicity studies using these materials are inconsistent in literature. The goal of this study was to examine the genotoxic potential of formocresol, paramonochlorophenol, and calcium hydroxide using mouse lymphoma cells and human fibroblasts cells in vitro by the comet assay. Data were assessed by Kruskal-Wallis nonparametric test. The results showed that all compounds tested did not cause DNA damage for the tail moment or tail intensity parameters. These findings suggest that formocresol, paramonochlorophenol, and calcium hydroxide do not promote DNA damage in mammalian cells and that the comet assay is a suitable tool to investigate genotoxicity.
Keywords: calcium hydroxide; formocresol; phenol derivative; animal cell; antibacterial activity; comet assay; controlled study; dentistry; DNA damage; fibroblast; genotoxicity; human; human cell; Kruskal Wallis test; lymphoma cell; nonhuman; Analysis of Variance; Animals; Calcium Hydroxide; Cell Survival; Cells, Cultured; Chlorophenols; Comet Assay; DNA Damage; Fibroblasts; Formocresols; Humans; Lymphoma; Mice; Mutagens; Root Canal Irrigants; Statistics, Nonparametric; Tumor Cells, Cultured